2022
DOI: 10.21037/jtd-22-1449
|View full text |Cite
|
Sign up to set email alerts
|

The roles and mechanisms of the lncRNA-miRNA axis in the progression of esophageal cancer: a narrative review

Abstract: Background and Objective: Esophageal cancer is one of the most common malignant digestive tract tumors. Despite various treatment methods, the prognosis of patients remains unsatisfactory, largely due to an insufficient understanding of the mechanisms involved in the pathogenesis and progression of esophageal cancer. More than 98% of the nucleotide sequences in the human genome do not encode proteins, and their transcription products are noncoding RNAs (ncRNAs), mainly long noncoding RNAs (lncRNAs) and microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…LncRNA expression patterns can change depending on the stage and subtype of cancer, and they can be very specific to particular tissues or cell types. As a result, choosing the right lncRNA target for a particular patient can be difficult (32,33).…”
Section: The Role Of Lncrnas In Ec Pathogenesismentioning
confidence: 99%
“…LncRNA expression patterns can change depending on the stage and subtype of cancer, and they can be very specific to particular tissues or cell types. As a result, choosing the right lncRNA target for a particular patient can be difficult (32,33).…”
Section: The Role Of Lncrnas In Ec Pathogenesismentioning
confidence: 99%
“…They are crucial components of the tumor microenvironment that participate in tumor initiation, progression, recurrence, metastasis, and resistance to chemotherapy [ 14 ]. A growing body of research has shown that CSCs are carcinogenic in most types of human cancers, including esophageal, breast, lung, liver, gastric, and pancreatic cancers [ 15 , 16 ]. LncRNAs play important roles in CSCs during tumor progression [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They usually participate in the biological process of cells at the transcription level, post-transcription level and epigenetic level. Among them, as a microRNA (miRNA) molecular sponge, regulation of miRNA to influence expression of related genes is one of the most important biological functions of lncRNAs [5,6] . Our previous study has found miRNA-140-5p expression significantly decreased during BMSCs' osteogenic differentiation process and which is promoted via miRNA-140-5p silence [7] .…”
mentioning
confidence: 99%